Exploration of stilbenoid trimers as potential inhibitors of sirtuin1 enzyme using a molecular docking and molecular dynamics simulation approach. Issue 31 (27th May 2021) - Abdjan, Muhammad Ikhlas; Aminah, Nanik Siti; Siswanto, Imam; Kristanti, Alfinda Novi; Takaya, Yoshiaki; Choudhary, Muhammad Iqbal
Abstract : A combination of molecular docking and molecular dynamics simulation (250 ns) has been carried out to study the interaction of stilbenoid trimer compounds with the SIRT1 enzyme as the target protein. Abstract : A combination of molecular docking and molecular dynamics simulation (250 ns) has been carried out to study the interaction of stilbenoid trimer compounds with the SIRT1 enzyme as the target protein. SIRT1 expression regulates cellular stress responses that lead to the development of cancer. Redocking showed a good native ligand pose with an RMSD value of 1.40 Å at the receptor active site's coordinates. The molecular docking score uses a grid score functional (kcal mol −1 ), which shows results of 1NS: 79.56, TS1: −26.83, TS2: −87.77, and TS3: −83.67. The TS2 and TS3 candidates were chosen for further analysis because they had a lower grid score than the native ligand (1NS). Furthermore, prediction of binding free energy (kcal mol −1 ) using the Quantum Mechanics/generalized Born Surface Area (QM/MM-GBSA) method shows the results of 1NS: −31.52 ± 0.39, TS2: −58.99 ± 0.34, and TS3: −43.38 ± 0.35. These results indicate that the TS2 and TS3 compounds have good potential as inhibitors of the SIRT1 enzyme. Additionally, the amino acid residues were responsible for the inhibition mechanism through hydrogen bond interactions at the molecular level, including ASP22, PHE91, PRO11, ILE165, ASP166, and VAL230. The observations made in this study provide theoretical information for exploring the stilbenoid trimers as anticancer agents by targeting the SIRT1 enzyme.